(3ZGjI GdMcje hCMb GdfJjLJjf HGdJYXjes - (3eSdeI Hf CMeO Hf bGSe Hf YHO Gddg GdeLQjWj, CHh GdbGSe,J (B398 (3g` s
(3ChdgG (B:s
(3CeG HYO, GdWGdH GdeZQe ai GdNhV ai Yde GdadGSaI hGdfXQ ai CSQGQge s
(3BNQgG (B:s
(3EP dG jchf ef HGH GdMceI HGH dWja hdGLdjd EdG hCjOJg GdMceG dJdGejPge hGOGQI ajeG Hjfge s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B234s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B243 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYQa YGeg (B- (3U (B155 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg HdOjI GdGScfOQjI (B((3L (B3720) s
Keywords: (3GdMQha h GdChaGbs